Harmonization of the fastest and densest responses reflects humanlike reaction time in mice - Kim, Chan Hee (Frontiers in Neuroscience, 2025)
IntroductionReaction time (RT) is important for evaluating delayed latency in behavior. Unlike humans, whose RT usually reflects a one-to-one stimulus–response relationship, the RT of animals can show two peaks representing the fastest and densest responses in the response distribution due to multiple responses per trial and can be further delayed depending on stimulus duration.MethodsStimulus duration was controlled to investigate whether these two peak latencies align to form a single RT. Sound cues lasting 10, 5, and 2 s, each associated with a food reward of condensed milk, were tested in three groups of 24 mice using delay conditioning paradigm. The frequency and latency of responses, along with basic indices such as accuracy, were analyzed.ResultsIn delay conditioning experiments using sound cues of 10, 5, and 2 s, the 2 s group exhibited the strongest positive correlations between the two peaks, as well as between the number of responses and accuracy rate, suggesting a coupling of the fastest and densest responses and a one-to-one relationship between stimulus and response.DiscussionBased on these findings, I propose harmonizing the two peaks, elicited by stimuli that induce prompt and minimal responses, as a criterion for designing animal experiments to better mimic humanlike RT.